A Note on the Occurrence of Solanum Hovei Dunal in India - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1973)
Solanum hovei Dunal (Solanaceae) a rare woody shrub endemic to North Western India has so far been known from its type collection from Dolca, sabermatty (Gujarat State) collected by A.P. Hove in the year 1819. Dunal 1852 described Hove's specimen as Solanum hovei Dunal. After 1852 this species has not been described in any Indian Flora viz., Clarke, 1883 and has not been reported from any where in India. This is now being reported for the first time during recent collections in Goa, during the coarse of our work on the preparation of Forest Flora of Goa. It is interesting and important to note that no authentic specimen of this taxon was available in Indian Herbaria till the confirmation of the present F.R.I. collection from British Museum, London. Its dispersal is attributed through migrant birds. Measures for conservation of this rare endemic are given.